PENGARUH TAYANGAN MODERN MOMS TRANS7 TERHADAP POLA ASUH DEMOKRATIS PADA IBU RUMAH TANGGA - Fadilah, Nur; Sudaryanto, Edy; Norhabiba, Fitri (Universitas 17 Agustus 1945 Surabaya, 2018)
Research seems to aim to find out the influence of the Modern Momsh program on the television station Trans7with the pololawasuhw democratic. The results showed the influence of the Trans7 Modern Mom variable on democratic parenting in housewives which was shown from the sig t test value under the real 0.05 rate, which means that there was a significant effect of Modern Moms impressions on the democratic parenting of research respondents. Correlation test results indicate a relationship of 0.896 which means there is a relationship of 89.6% of Modern Moms shows with democratic parenting.Based on the results of the study, it appears that television, especially the modern film, can give influence to viewers, so that it can be concluded that television is an effective medium in influencing viewers.Keywords: democratic parenting, impressions, cultivation